Canadian International Petroleum Conference 2007
DOI: 10.2118/2007-015
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Acid Reaction Rates With the Rotating Disk Apparatus)

Abstract: The authors have published several papers on the rotating disk apparatus (RDA) in recent years. The RDA is used to measure acid reaction rates, reaction order and activation energy of acidizing fluids with carbonate reservoir rock. This paper summarizes the different ways that acid reaction rates are measured, the factors that affect the results and why this is important when modelling acid stimulation treatments in the field.In particular, experimental procedures used to obtain acid reaction rates vary widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Samples were collected every 2 minutes for the first 10 minutes, then every 5 minutes for 25 minutes, and the two final samples after 45 minutes and 50 minutes, respectively. Corrections were made to account for changes in the volume of the reactants that occurred because of sample withdrawal (24,25) . The rotating disk experiments were conducted to determine the effects of initial citric acid concentration (1 wt%, 2 wt%, 5.0 wt% and 7.5 wt%), temperature (25°C, 40°C and 50°C) and rotational speed (100 rpm -1,000 rpm) on the calcite dissolution rate.…”
Section: Rotating Disk Apparatus (Rda)mentioning
confidence: 99%
“…Samples were collected every 2 minutes for the first 10 minutes, then every 5 minutes for 25 minutes, and the two final samples after 45 minutes and 50 minutes, respectively. Corrections were made to account for changes in the volume of the reactants that occurred because of sample withdrawal (24,25) . The rotating disk experiments were conducted to determine the effects of initial citric acid concentration (1 wt%, 2 wt%, 5.0 wt% and 7.5 wt%), temperature (25°C, 40°C and 50°C) and rotational speed (100 rpm -1,000 rpm) on the calcite dissolution rate.…”
Section: Rotating Disk Apparatus (Rda)mentioning
confidence: 99%
“…Samples were collected every 2 minutes for the first 10 minutes; and then every 5 minutes for 25 minutes; and the two final samples after 45 and 50 minutes, respectively. Corrections were made to account for changes in the volume of the reactants that occurred due to sample withdrawal (21,22) . The rotating disk experiments were conducted to determine the effects of initial citric acid concentration (1, 2, 5.0, 7.5 wt%), temperature (25, 40, 50°C), and rotational speed (100-1,000 rpm) on the calcite dissolution rate.…”
Section: Rotating Disk Apparatus (Rda)mentioning
confidence: 99%
“…Taylor et al measured the reaction rate between deep dolomitic gas reservoirs with hydrochloric acid at different temperatures. They also concluded that acid reactivity varies highly by rock composition [6,7].…”
Section: Introductionmentioning
confidence: 99%